Indonesian Interrogative Sentences: a Study of Forms and Functions - Lindawati Lindawati (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2016)
This study examines Indonesian interrogative sentence problems by focusing on issues of forms and functions. The data used in this analysis are interrogative sentences in Indonesian language that are currently used in oral and in interethnic communication. This study used a pragmatic approach. Listening while observing (metode simak) is used at the stage of data collection. In the analysis phase, a structural analysis is used for the discussion of issues related to the form, and a contextual analysis method is used for the discussion of issues related to the function of interrogative sentence. The report was presented verbally. From the research, it can be formulated that interrogative sentences forming elements are either supra-segmental elements or segmental elements. Supra-segmental elements are intonation, and segmental elements are words, phrases, and particles. The elements were added to a clause to be the base of an interrogative sentence. Based on the response form provided by what the opponents said, interrogative sentences are grouped on the yes-no and information interrogative sentences. Yes-no interrogative sentences require an answer that contains a justification or denial of what is stated on the clause that is the basis for the formation of interrogative sentences. Information interrogative sentences require an answer in the form of explanation. In communications, interrogative sentences are uttered not only to ask something, but they are also used to express a variety of speech act. Speech act that can be expressed by the interrogative sentences of Indonesian language are representative, directive, commissive, and expressive. Interrogative sentences are sometimes used in order to speak indirectly (indirect speech) to maintain politeness or otherwise stated expressive rudely.